The effects of temperature and transmembrane pressure on protein, calcium and plasmin partitioning during microfiltration of skim milk. (March 2021) - France, Thomas C.; Kelly, Alan L.; Crowley, Shane V.; O'Mahony, James A.
Abstract: Dissociation of β-casein from casein micelles at low temperature is exploited in the manufacture of β-casein-enriched ingredients. In this study, the effects of selected temperatures within the cold processing range (4, 8, 12, 16 and 20 °C) and different transmembrane pressures (0.05 and 0.30 bar), on protein, mineral and plasmin partitioning during microfiltration were determined. Significantly higher ( p < 0.05) total and ionic calcium concentrations were measured in permeate generated at 4 °C under sub-critical flux conditions (0.05 bar) compared with limiting flux conditions (0.30 bar). Under the former, the highest concentration of β-casein in permeate (2.02 mg mL −1 ) was achieved at 4 °C; however, these conditions also led to the highest plasmin activity (0.023 AMC units mL −1 ) in permeate. Lower processing temperature and reduced fouling contribute to higher yields of β-casein, although the concomitantly higher plasmin activity may contribute to protein stability challenges during down-stream processing of such permeates.